THE ECONOMIC EMPOWERMENT OF CHILD LABOUR IN FAMILY BUSINESS AT CIBADUYUT FOOTWEAR INDUSTRY - Sumardani Sumardani; Yuyun Yuningsih (Universitas Pasundan, 2019)
Child labour tend to have high hazards and risks especially when they grind and glue a sole tothe upper part of the shoes. Shoes making remains to be a hazardous work for children and adults as long as chemical-based solvents are used. To overcome these problems, the goverment of the Republic of Indonesia launched a program by giving some aids to the parents of the child laborer to run their small business so that their children can stop working at the shoemaking industry.This research aims at analyzing the economic empowerment of parents who employed their children in the online business industry at Cibaduyutfootwear industry and use a qualitative approach with a triangulation of data collected. The research informants were the child laborer, parents who employed their children, footwear craftsmen, and the Head of Industry and Trade Agency. The results of this research showed that economic empowerment in child laborer’sparents was still in low level and they could not market their shoes properly as a product of their smallbusiness. In this context, they need both training and workshop in social entrepreneurship and online business method in order to promote their product.